2016
DOI: 10.1016/j.tjog.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of vitamin D and omega-3 polyunsaturated fatty acids on experimental endometriosis

Abstract: Omega-3 PUFA caused significant regression of endometriotic implants. Vitamin D has not been as effective as omega-3 PUFA on endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 17 publications
1
32
0
3
Order By: Relevance
“…In particular, the 12/15-12/15-lipoxygenase-pathway metabolites of eicosapentaenoic acid seem to be important mediators to suppress the progression of implants (150). A further study in rat showed that omega-3 polyunsaturated fatty acids induced lesions regression more than 1,25dihydroxyvitamin-D3 (151). A cohort of women with endometriosis was treated for three months with a combination of antioxidants, including omega -3 and-6 fatty acids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular, the 12/15-12/15-lipoxygenase-pathway metabolites of eicosapentaenoic acid seem to be important mediators to suppress the progression of implants (150). A further study in rat showed that omega-3 polyunsaturated fatty acids induced lesions regression more than 1,25dihydroxyvitamin-D3 (151). A cohort of women with endometriosis was treated for three months with a combination of antioxidants, including omega -3 and-6 fatty acids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…46 Additionally, the vitamin has been implicated in a number of pathologies affecting women, 7,8 including polycystic ovary syndrome (PCOS), 911 yet little is known about how it affects androgen homeostasis in premenopausal, eumenorrheic women.…”
mentioning
confidence: 99%
“…Akyol et al [34] исследовали влияние ви-тамина D и омега-3 ПНЖК (полиненасыщен-ных жирных кислот) на экспериментально ин-дуцированный эндометриоз на модели крыс. Слепое рандомизированное контролируемое экспериментальное исследование было про-ведено на 30 самках крыс Wistar.…”
Section: данные о роли витамина D в патогенезе наружного генитальногоunclassified
“…Уровни IL-6, TNF-α и ва-скуло-эндотелиального фактора роста (VEGF) в перитонеальной жидкости также были зна-чительно снижены в конце лечения в группе, получавшей омега-3. В группе, получавшей ви-тамин D, значительно снижен был только уро-вень IL-6 [34].…”
Section: данные о роли витамина D в патогенезе наружного генитальногоunclassified